(untitled) (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: Breastfeeding (BF) is a socially constructed and controlled practice. Although breastfeeding is a common practice in Nepal, proper breastfeeding is on the decline due to several factors. The impact of knowledge and attitude about breastfeeding practice, i.e., duration of breastfeeding, proper techniques, proper time of weaning is poorly understood. So, this study is designed to assess the knowledge, attitude and practice of mothers in breastfeeding. Material and Methods: This is an observational descriptive cross sectional study carried out among 220 mothers of under 2 years old children attending the pediatric out-patient department (OPD) at Janaki Medical College teaching hospital (JMCTH), Janakpur, Nepal. Mothers were interviewed using pre-designed questionnaire constructed after proper literature review. Results: All mothers have idea that they have to breast feed their babies, but they did not have adequate knowledge on the appropriate way of breastfeeding. Only, 12.27% knew that they have to initiate breast feeding within 1 hour of birth, 15% had idea on pre-lacteal feed, 5% had idea on importance of colostrum, 10% knew the meaning of exclusive breast feeding, and 0% of the mothers had idea on importance of night feeding. Only 7.27% have knowledge on method on maintaining aseptic precaution during breastfeeding. Only 20.90% were practicing exclusive breast feeding, 70% mothers were practicing night feeds, 15% mothers practiced feeding one side at a time and 15% mothers were practicing appropriate attachment and positioning during BF. None of the mothers got any advice regarding breast feeding during antenatal care (ANC) visits. Only 15% mothers got proper method of breastfeeding advice after birth. 30% practiced burping after breastfeeding. 30% underwent practice of proper food to increase breast milk secretion. Conclusion: Undesirable cultural practices such as late initiation of breastfeeding after birth, giving pre-lacteal feeds, delay in introduction of weaning foods, not exercising exclusive breastfeeding practice are still prevalent. The maternal knowledge, attitude and practice (KAP) in breastfeeding is still inadequate with a big gap between actual and desired practices and there is urgent need of mother educational program in this society.